The dual blocker of FAAH/TRPV1 N-arachidonoylserotonin reverses the behavioral despair induced by stress in rats and modulates the HPA-axis - Navarria, Andrea; Tamburella, Alessandra; Iannotti, Fabio A; Micale, Vincenzo; Camillieri, Giovanni; Gozzo, Lucia; Verde, Roberta; Imperatore, Roberta; Leggio, Gian Marco; Drago, Filippo; Di Marzo, Vincenzo (Pharmacological research, 2014)
In recent years, several studies have explored the involvement of the deregulation of the hypothalamus-pituitary-adrenal (HPA) axis in the pathophysiology of stress-related disorders. HPA hyper-activation as a consequence of acute/chronic stress has been found to play a major role in the neurobiological changes that are responsible for the onset of such states. Currently available medications for depression, one of the most relevant stress-related disorders, present several limitations, including a time lag for treatment response and low rates of efficacy. N-Arachidonoylserotonin (AA-5-HT), a dual blocker at fatty acid amide hydrolase (FAAH, the enzyme responsible for the inactivation of the endocannabinoid anandamide) and transient receptor potential vanilloid type-1 channel (TRPV1), produces anxiolytic-like effects in mice. The present study was designed to assess the capability of AA-5-HT to reverse the behavioral despair following exposure to stress in rats and the role of the HPA-axis. Behavioral tasks were performed, and corticosterone and endocannabinoid (anandamide and 2-arachidonoylglycerol) levels were measured in selected brain areas critically involved in the pathophysiology of stress-related disorders (medial PFC and hippocampus) under basal and stress conditions, and in response to treatment with AA-5-HT. Our data show that AA-5-HT reverses the rat behavioral despair in the forced swim test under stress conditions, and this effect is associated with the normalization of the HPA-axis deregulation that follows stress application and only in part with elevation of anandamide levels. Blockade of FAAH and TRPV1 may thus represent a novel target to design novel therapeutic strategies for the treatment of stress-related disorders.
Keywords: Endocannabinoids; systém hypotalamus-hypofýza; chování zvířat; TRPV Cation Channels; potkani Wistar; kortikosteron; Arachidonic Acids; kationtové kanály TRPV; Corticosterone; endokanabinoidy; Male; plavání; Hypothalamo-Hypophyseal System; Brain; Polyunsaturated Alkamides; glyceridy; polynenasycené alkamidy; Rats, Wistar; Brain-Derived Neurotrophic Factor; kyseliny arachidonové; amidohydrolasy; krysa rodu Rattus; Restraint, Physical; Stress, Psychological; Rats; Glycerides; psychický stres; fyzické omezení; Behavior, Animal; Serotonin; Amidohydrolases; serotonin; mozek; zvířata; mužské pohlaví; mozkový neurotrofický faktor; Pituitary-Adrenal System; Animals; systém hypofýza - nadledviny; Swimming